Enhancing newborn screening sensitivity and specificity for missed NICCD using selected amino acids and acylcarnitines - Peiyao Wang; Lingwei Hu; Yuhe Chen; Duo Zhou; Shasha Zhu; Ting Zhang; Ziyan Cen; Qimin He; Benqing Wu; Xinwen Huang (Orphanet Journal of Rare Diseases)
Abstract Purpose To enhance the detection rate of Neonatal Intrahepatic Cholestasis caused by Citrin Deficiency (NICCD) through newborn screening (NBS), we analyzed the metabolic profiles of missed patients and proposed a more reliable method for early diagnosis. Methods In this retrospective study, NICCD patients were classified into “Newborn Screening” (64 individuals) and “Missed Screening” (52 individuals) groups. Metabolic profiles were analyzed using the non-derivatized MS/MS Kit, and genetic mutations were identified via next-generation sequencing and confirmed by Sanger sequencing. Receiver Operating Characteristic (ROC) analysis evaluated the predictive value of amino acids and acylcarnitines in dried blood spots (DBS) for identifying missed patients including 40 missed patients and 17,269 healthy individuals, with additional validation using 12 missed patients and 454 healthy controls. Results The age of diagnosis was significantly higher in the “Missed Screening” group compared to the “Newborn Screening” group (74.50 vs. 18.00 days, P < 0.001). ROC analysis revealed that citrulline had excellent diagnostic accuracy for missed patients, with an AUC of 0.970 and a cut-off value of 17.57 µmol/L. Additionally, glycine, phenylalanine, ornithine, and C8 were significant markers, each with an AUC greater than 0.70. A combination of these markers achieved an AUC of 0.996 with a cut-off value of 0.00195. Validation demonstrated a true positive rate of 91.67% and a true negative rate of 96.48%. Common SLC25A13 mutations in both groups were c.852_855del, IVS16ins3kb, and c.615 + 5G > A. Conclusions Combining multiple metabolic markers during NBS significantly improves sensitivity and specificity for detecting missed NICCD cases. However, the relationship between genetic mutations and missed cases remains unclear.